Fostering Energy Saving Potential Through Preliminary Energy Audit in Fuel Terminal: A Case Study - Oktasio Fahlevi; Todo Hotma T Simarmata; Ginanjar Indra Maulana (International Journal Labs, 2026)
The energy audit is a method for analyzing energy use patterns in a facility and identifying potential efficiency improvement opportunities. In this study, level 2 of the energy audit was conducted at one of Indonesia's fuel terminals. The energy performance indicator (ENPI) was calculated over three years. The ENPI of the fuel terminal increased from 2022 to 2024, indicating that energy consumption per unit of production (kL) rose year by year. The increase from 2022 to 2023 was 27%, while that from 2023 to 2024 was 14%. A higher ENPI value indicates greater energy consumption to produce each kiloliter of product. The implementation of energy conservation opportunities is expected to reduce energy consumption by an average of 5–10% per month, equivalent to approximately 35,784–48,585 kWh per month, and can also reduce CO? emissions by 298.14 TonCO?Eq using an emission factor of 0.83. In order to implement an energy management system, the organization must establish a supporting system, particularly an energy policy that defines the company’s general energy-related policies.